Orthodontic camouflage of skeletal Class III malocclusion with miniplate: a case report - Farret,Marcel Marchiori (2016)
ABSTRACT Introduction: Skeletal Class III malocclusion is often referred for orthodontic treatment combined with orthognathic surgery. However, with the aid of miniplates, some moderate discrepancies become feasible to be treated without surgery. Objective: To report the case of a 24-year-old man with severe skeletal Angle Class III malocclusion with anterior crossbite and a consequent concave facial profile. Methods: The patient refused to undergo orthognathic surgery; therefore, orthodontic camouflage treatment with the aid of miniplates placed on the mandibular arch was proposed. Results: After 18 months of treatment, a Class I molar and canine relationship was achieved, while anterior crossbite was corrected by retraction of mandibular teeth. The consequent decrease in lower lip fullness and increased exposure of maxillary incisors at smiling resulted in a remarkable improvement of patient's facial profile, in addition to an esthetically pleasing smile, respectively. One year later, follow-up revealed good stability of results.